2003
DOI: 10.1016/s0016-5107(03)70107-2
|View full text |Cite
|
Sign up to set email alerts
|

Systematic evaluation of complications related to endoscopy in a training setting: A prospective 30-day outcomes study

Abstract: Serious adverse events were rare after endoscopy performed by gastroenterology fellows. Contacting patients 30 days after outpatient endoscopy significantly improved the detection of negative outcomes. Although the majority of negative outcomes were minor, these adverse events were associated with decreased patient satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 0 publications
1
19
2
Order By: Relevance
“…This is prolonged compared with some reports in the literature from expert technical colonoscopists,28 but in line with studies of routine clinical practice which report times from 7-11 minutes 7, 11, 18, 21, 29, 30. The immediate complication rate of 0.4% that we detected, however, is consistent with other estimates in the literature,4, 5, 7 with the caveat that retrospective series often underestimate the total number of procedural complications 6. Our overall cecal intubation rate, too, was similar to those rates previously reported in the literature (most of which range between 91 and 99%, depending on the study setting and colonoscopy indication),5, 7, 12, 13, 15-19, 30 and met the goal set forth by the U.S. Multi-Society Task Force on Colorectal Cancer 31…”
Section: Discussionsupporting
confidence: 91%
“…This is prolonged compared with some reports in the literature from expert technical colonoscopists,28 but in line with studies of routine clinical practice which report times from 7-11 minutes 7, 11, 18, 21, 29, 30. The immediate complication rate of 0.4% that we detected, however, is consistent with other estimates in the literature,4, 5, 7 with the caveat that retrospective series often underestimate the total number of procedural complications 6. Our overall cecal intubation rate, too, was similar to those rates previously reported in the literature (most of which range between 91 and 99%, depending on the study setting and colonoscopy indication),5, 7, 12, 13, 15-19, 30 and met the goal set forth by the U.S. Multi-Society Task Force on Colorectal Cancer 31…”
Section: Discussionsupporting
confidence: 91%
“…There is some evidence that patients experiencing complications after endoscopy are less satisfied and less likely to return for a repeat endoscopy. 54 As endoscopy complications are rare, this would require a sample much larger than in the present study. Another possible approach would be to correlate the patient satisfaction data with the change in SF-36 scores at 1 day after endoscopy and see whether patients reporting higher satisfaction levels have better general health.…”
Section: Discussionmentioning
confidence: 95%
“…10,11 Bini et al showed that there is a significant association between negative outcomes and decreased satisfaction in patients undergoing colonoscopy. This is usually because of the perceived lack of clinical relevance of these symptoms given that they are usually mild and self-limiting.…”
Section: Discussionmentioning
confidence: 99%